The Influence Of Intellectual Intelligence And Academic Self Efficacy On Academic Fraud With Student Ethical Attitude As A Moderating Variable - Marques, Ivete; Komiya, Kazutaka; Rosary, Lorraine Rayelle Gomesª (Journal of Management, 2022)
The goal of this study is to determine how intellectual ability and self-efficacy influence academic cheating behavior, with students' ethical attitudes serving as a moderating factor. The research was conducted using a quantitative methodology. The population of this study consisted of 65 students enrolled in the Management Study Program at Widyatama University in West Java in 2018. Data analysis was carried out using Warp PLS 7.0 software's partial least squares (PLS), and sampling was done using simple random sampling. The research results and hypothesis testing demonstrate that the intellectual intelligence variable has a detrimental impact on academic cheating, with a path coefficient of -0.455 and a P-value of 0.001. In the self-efficacy measure, the path coefficient is also -0.377 with a P-value of 0.001. The results of the test of the moderating variable on academic cheating were a path coefficient of 0.205 and a P value of 0.036, as well as a path coefficient of 0.502 and a P value of 0.001, which showed that the variables attitude and intellectual intelligence had a negative and significant impact. These two factors' propensity for academic cheating can be moderated by student ethics.